HUBUNGAN SHIFT KERJA DAN BEBAN KERJA TERHADAP KELELAHAN KERJA PADA PT. X KOTA JAMBI TAHUN 2023 - Nabila Afifah; Renny Listiawaty; Eti Kurniawati (Bajang Institute, 2024)
Background: Work accidents are influenced by five interrelated factors, namely working conditions, manufacturing negligence, unsafe acts, accidents and injuries. Work environment factors that do not meet Occupational Safety and Health (K3) requirements, unsafe work processes, and increasingly complex and modern work systems can pose a threat to workers' safety and health. Working conditions are influenced by several things, including workload, work shifts, the temperature of the working environment and the period during which the work is carried out. To find out the relationship between work shifts and workload on work fatigue in workers at PT. X. Method: This type of research is quantitative with a cross sectional design. The total sample population is 58 respondents. Data collection uses questionnaires and observations. Sampling used the Total Sampling technique. Data analysis was carried out univariate and bivariate. Results: Based on statistical tests using chi-square, length of service obtained a P-value = 0.000 (P<0.05), workload obtained a P-value = 0.000 (P<0.05) and work environment obtained a P-value value = 0.007 (P<0.05) statistically shows that work period and workload have a significant relationship with work fatigue at PT. X Jambi City and work environment with work fatigue are not related at PT. X Jambi City. Conclusion: It is recommended for companies to avoid fatigue at work in order to avoid work accidents by explaining to each new worker about the conditions and dangers that can arise in the workplace with safe ways and attitudes in carrying out their work